OP64 Preconceptional maternal anxiety is associated with childhood emotional problems, independent of the effect of post-natal depression. (13th September 2016) - Baird, J; Jarman, M; Robinson, SM; Lawrence, WT; Barker, ME; Godfrey, KM; Cooper, C; Inskip, HM
Abstract : Background: Maternal perinatal depression has been associated with behavioural problems in their children. In the ALSPAC cohort, ante- and post-natal depression had independent effects on child behaviour at 4 years. The strongest risk factor for maternal perinatal depression is pre-existing anxiety or depression suggesting that women with perinatal depression might have experienced mental health problems in the preconceptional period. We examined the association between maternal anxiety in the preconceptional period and childhood behaviour at 3 years of age in the Southampton Women's Survey (SWS). Methods: The SWS is a population based cohort study of 12, 583 women aged 20 to 34 years who were assessed when not pregnant. Women who subsequently became pregnant and their children (n = 3158) were followed up. All women enrolled during the latter half of recruitment completed the General Health Questionnaire (GHQ-12), a short screening instrument with good sensitivity for depression and anxiety disorders; a score ≥3 was categorised as positive for significant psychological distress. At 3 years, child behaviour was assessed with the Strengths and Difficulties Questionnaire administered to parents and used to characterise hyperactivity, conduct disorders and emotional problems; standard definitions were used for borderline and definite cases of each behavioural problem. Prevalence ratios for child behaviour problems, adjusted for the influence of potential confounding factors, were obtained using binary regression. Results: Of 1, 518 children (52% boys) followed to age 3 years of age, whose mothers had completed the GHQ-12 before pregnancy, 290 (19%) had hyperactivity, 366 (24%) had conduct disorders and 499 (19%) had emotional problems. 27% of mothers had evidence of preconceptional distress and 42% of postnatal depressive symptoms. In univariate analyses, preconceptional distress was associated with a 48% increased risk of emotional problems [prevalence ratio (PR) 1.48 (95% CI: 1.19, 1.94)]. In analyses adjusted for potential confounding factors (postnatal depression, maternal educational attainment, receipt of benefits, number of children, sleep duration and maternal work), preconceptional distress was associated with a 36% increased risk of emotional problems [PR 1.36 (95% CI: 1.08, 1.71)]. Maternal preconceptional distress was not associated with either hyperactivity or conduct disorders at 3 years of age. Conclusion: We found that maternal preconceptional mental health problems are associated with emotional problems among their children at 3 years of age, independent of the effect of postnatal depression and other confounding factors. These findings suggest that recognition of women with psychological distress during preconception might facilitate the prevention of childhood emotional problems.